2008
DOI: 10.1016/j.vaccine.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of otitis media: A moving target

Abstract: The microbiology of acute otitis media (AOM) is linked to the nasopharyngeal commensal flora. This respiratory ecosystem undergoes various selective pressures, such as antibiotic consumption and vaccine use. Socio-economic conditions also influence the bacterial composition of the nasopharynx. Streptococcus pneumoniae, non-encapsulated Haemophilus influenzae, Moraxella catarrhalis, and group A Streptococcus are the leading causes of bacterial AOM worldwide. This paper will discuss the causes and consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 57 publications
(65 reference statements)
0
76
1
2
Order By: Relevance
“…URTI causes nasopharyngitis which affects the Eustachian tube (ET), as a result negative pressure is created and that causes suction of the mucus of the nasopharynx inside the middle ear; that explains why aspirate of AOM can show bacteria like Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis [2,8], which are commensal to nasopharynx [16]. The initial course of the disease is thought to be viral in origin with bacterial superinfection occurs after that [2,12], many viruses have been implemented as a causative agents which are found in 90 % of AOM cases, like rhinovirus, coronavirus, enterovirus, respiratory syncytial virus (RSV), parainfluenza type 1, 2 or 3, influenza A or B, and adenovirus [1,2,7,14,17].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…URTI causes nasopharyngitis which affects the Eustachian tube (ET), as a result negative pressure is created and that causes suction of the mucus of the nasopharynx inside the middle ear; that explains why aspirate of AOM can show bacteria like Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis [2,8], which are commensal to nasopharynx [16]. The initial course of the disease is thought to be viral in origin with bacterial superinfection occurs after that [2,12], many viruses have been implemented as a causative agents which are found in 90 % of AOM cases, like rhinovirus, coronavirus, enterovirus, respiratory syncytial virus (RSV), parainfluenza type 1, 2 or 3, influenza A or B, and adenovirus [1,2,7,14,17].…”
Section: Pathogenesismentioning
confidence: 99%
“…Streptococcus pneumonia is the most common and found in 35-45% [3,20], patients infected with this microorganism tend to have more severe disease [3,16]. The serotypes responsible have been changed after the introduction of pneumococcal 7-valent conjugate vaccine (PCV7) [3].…”
Section: Streptococcus Pneumoniae Haemophilus Influenzae Andmentioning
confidence: 99%
“…Hassett et al reported the annual number of Americans affected by COPD in 2014 at over 14 million [6]. OM is the most common pediatric infectious disease in humans accounting for over 20 million physician visits and costing the U.S. upwards of 5 billion dollars annually [7,8]. OM is characterized by mucous overproduction and inflammation in the middle ear cavity due to infection.…”
Section: Introductionmentioning
confidence: 99%
“…OM is characterized by mucous overproduction and inflammation in the middle ear cavity due to infection. Pediatric patients are highly susceptible to OM pathogens due to the shortened length of the Eustachian tube during development [7]. Currently, the standard treatment for both COPD and OM is systemically administered broad-spectrum antibiotics, which, leads to increased antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The middle ear infection (otitis media) is the most common pediatric infectious disease and is the most common reason for physician's office visits and antibiotic prescriptions [1]. It was estimated to cost the US alone roughly five billion dollars per year for the management of otitis media (OM) in 1996 [2].…”
Section: Introductionmentioning
confidence: 99%